Gender, ethnic identity and work - Amelie F. Constant; Liliya Gataullina; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2006)
The European Union's strategy to raise employment is confronted with very low work participation among many minority ethnic groups, in particular among immigrants. This study examines the potential of immigrants' identification with the home and host country ethnicity to explain that deficit. It introduces a two-dimensional understanding of ethnic identity, as a combination of commitments to the home and host cultures and societies, and links it to the labour market participation of immigrants. Using unique German survey data, the paper identifies marked gender differences in the effects of ethnic identification on the probability to work controlling for a number of other determinants. While ethnically assimilated immigrant men outperform those who are ethnically separated and marginalized, they are not different from those with openness to both cultures. Assimilated immigrant women do better than those separated and marginalized, but those who develop an attachment to both cultures clearly fare the best.
urn:nbn:de:101:1-2009030986
Keywords: 330